A novel "signal on" photoelectrochemical strategy based on dual functional hemin for microRNA assay. Issue 65 (29th July 2019) - Xia, Ling-Ying; Li, Meng-Jie; Wang, Hai-Jun; Yuan, Ruo; Chai, Ya-Qin
Abstract : Here, a novel "signal on" photoelectrochemistry (PEC) biosensor was constructed by dual functional hemin as signal quencher and electronic mediator for ultrasensitive target microRNA-141 assay with the assistance of T7 exonuclease (Exo)-initiated target amplification technology. Abstract : In this work, a novel "signal on" photoelectrochemistry (PEC) biosensor was constructed with dual-functional hemin as a signal quencher and electronic mediator for ultrasensitive target microRNA-141 assay with the assistance of T7 exonuclease (Exo)-initiated target amplification technology.